PENERAPAN TOGAF ADM UNTUK PERENCANAAN ENTERPRISE ARCHITECTURE SISTEM INFORMASI PADA UPT BKN JAMBI - Putra, Sumpena Adi; Roestam, Rusdianto (LPPM Universitas Dinamika Bangsa, 2020)
Indonesia's governance to open government is a must do to provide information disclosure to the public. Inthis case, UPT BKN Jambi as the leading guard has the vision and mission to carry out the staffing serviceapproach to the region area of Jambi province, such as transform business functions towards digitalization,but to realize this, UPT BKN Jambi doesn’t have enterprise architecture documentation yet to be guidelinesfor realized information systems development based on business functions and user needs. Therefore, itneeds a planning to define and identify business needs, data, applications, and technologies that canrepresent a enterprise architecture. This planning must have steps and methodologies can be used to helpanalyze organizational unit needs. TOGAF ADM as a method used to develop the planning, designing,implementation, management, and implementation of information system architecture governance. Steps of 4domains of information system architecture development, namely : business architecture, data architecture,application architecture, and technology architecture are applied to produce blueprint documentation thatcan be guidelines realized of an integrated information system based on the change and needs of theorganizational development forward